Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.17509/jtikor.v3i1.11276
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Program Kebugaran Daya Tahan Kardiovakular Berbasis Android

Abstract: Abstrak _________________________________________________________Tujuan penelitian ini adalah merancang aplikasi android sebagai alat bantu program kebugaran daya tahan kardiovaskular. Aplikasi ini terdapat 3 fitur utama yaitu memberi edukasi tentang kebugaran, membantu dalam pengetesan VO2Max, dan membantu dalam pembuatan program latihan kebugaran daya tahan kardiovaskular secara otomatis. Penelitian ini menggunakan metode penelitian Research and Development yang dilakukan dalam enam tahap. Adapun tahap-tahap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…The results of this study are in line with the study of (Iyakrus, 2012b), which in his research concluded that the development of a physical training model for sepaktakraw athletes produces effective products that can improve the physical components of athletes. Furthermore, (Putro, 2018) created the GO FIT application as a tool for cardiovascular endurance fitness programs. Then the results of the analysis of application trials with the percentage of feasibility level of 88.41% are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with the study of (Iyakrus, 2012b), which in his research concluded that the development of a physical training model for sepaktakraw athletes produces effective products that can improve the physical components of athletes. Furthermore, (Putro, 2018) created the GO FIT application as a tool for cardiovascular endurance fitness programs. Then the results of the analysis of application trials with the percentage of feasibility level of 88.41% are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Nike Training Club application has a significant effect on the endurance of futsal extracurricular players (Faozi & Rahmawati, 2019). According to Putro et al (2018), he also stated that the Android application was designed as a tool for cardiovascular endurance fitness programs and there are 3 main features, namely providing education about fitness, assisting in VO2max testing, and assisting in making cardiovascular endurance fitness training programs automatically. In addition, the fartlek training method is an excellent form of training to increase endurance in almost all sports (Pratama et al, 2022;Pribadi et al, 2022).…”
Section: Figure 2 Physical Condition (Vo2max) Of Pusaka Fc Club Ball ...mentioning
confidence: 99%
“…This product contains general fitness information using the VO2max test method, the process of calculating values by classification, and research results with feasibility values. of 88.41% [5]. Aji [6] also developed a ladder tool for coordination, agility, and power exercises obtained from the validation results from material experts of 86% or feasible; media expert by 80% or appropriate; small group trials of 84.42% or appropriate; large group trials of 82.12% or appropriate.…”
Section: Previous Researchmentioning
confidence: 99%